Salience, Perceptual Dimensions, and the Diversion of Attention. - KUMAR, KIRAN N.; CHANDRAMOULI, SUYOG H.; SHIFFRIN, RICHARD M. (American Journal of Psychology)
Parallel and automatic processing is evidenced in visual search by what is commonly called popout. An object of search (a target) that differs widely from all other display objects on some simple visual dimension is commonly called a singleton; an example is search for a red circle when all other displayed circles are green. A singleton attracts attention to the degree that it is salient, and highly salient singletons produce search that is almost independent of display size. The present research examines the way this attraction of attention can be diverted by the presence of singletons on 1 or 2 nontarget perceptual dimensions (e.g., search for a red circle among green ones, when one of the green circles is larger than the others, and another might be green but square). The results establish that distraction occurs rarely but strongly, that 2 distractors produce more distraction than 1, and that the degree of distraction depends not only on salience but also on dimension similarity. These findings occurred in 2 different tasks: The observer either reported the orientation of a Gabor embedded in the target or reported the presence and absence of the target.